Innovation and entrepreneurship: practice and principles - Drucker, Peter F. (New York, 1985)
"This is the first book to present innovation and entrepreneurship as a purposeful and systematic discipline that explains and analyzes the challenges and opportunities of America's new entrepreneurial economy. Superbly practical, Innovation and Entrepreneurship explains what established businesses, public service institutions, and new ventures need to know and do to succeed in today's economy."